Lipid-induced cardiovascular diseases - Manandhar, Sumeet; Ju, Sujin; Choi, Dong-Hyun; Song, Heesang (Journal of Cardiology and Cardiovascular Medicine, 2017)
Cardiovascular diseases are the leading cause of death worldwide. There are many evidences that the dysfunctioning lipotoxicity is the one of major factors of cardiovascular diseases such as, atherosclerosis, hypertension, and coronary heart disease. Obesity and diabetes increase circulating lipids that are likely with more generation of toxic intermediates, which leading to the complications associated with cardiovascular diseases. Indeed, lipotoxicity is a metabolic syndrome caused by abnormal lipid accumulation, which leads to cellular dysfunction and necrosis. Here we review the factors that induced pathogenesis of cardiovascular diseases by lipid accumulation and the mechanisms underlying the lipotoxicity.